DESAIN LKPD MENGGUNAKAN PENDEKATAN ETNOSAINS UNTUK MENINGKATKAN KEMAMPUAN LITERASI KIMIA PESERTA DIDIK - Khasanah, Wahyu Uswatun; Sumarni, Woro (Universitas Negeri Semarang, 2021)
The indonesian students scientific literacy is still lower than the other students in another countries based on PISA 2018 which is ranked 70 from 78 countries. Enhancing the chemical literaty abilities of studentss ethnoscience approached worksheet. This study aim to improve students chemical literacy. The subject of this study is students of XI MIPA 6 of SMA N 2 Ungaran. The design of thi study is 4D development model. Pretest and posttest were used to measured improvements in chemical literacy on each aspect. The ethnoscience approached worksheetis declared worhty to use based on validation of 3 judges, the result of material validations is 92.02% and media validation is 93.39%. This worksheet received positive responses from students, the results are 42.8% of students response very well, 54.8% of students response well. From the pretest and posttest analysis, the chemical literacy ability of students, the N-Gain value content aspect is 0.62, the N-Gain value context aspect is 0.57, and the N-Gain value competency aspect is 0.64. based on the results of the study, the developed ethnoscience approached of students worksheet was feasible and well received by students.